DIFFERENTIAL DIAGNOSTICS OF ABDOMEN LYMPHADENOPATHY IN HIV PATIENTS - M. V. Sinitsyn; M. S. Skopin; M. N. Reshetnikov; D. V. Plotkin; Yu. R. Zyuzya; I. A. Sokolina (Туберкулез и болезни лёгких)
The objective of the study: to investigate the specific features of intra-abdominal lymphadenopathy in HIV positive patients, to define the best differential diagnostic criteria.Subjects and methods. Medical records of 113 HIV positive patients with intra-abdominal lymphadenopathy for 2012-2017 were retrospectively analyzed. The patients underwent the comprehensive examination including X-ray and endoscopy, laboratory assays, tests of biopsy specimens collected from lymph nodes, microbiological and molecular genetic tests.Results. Due to this comprehensive examination, which included invasive diagnostics, etiology of intra-abdominal adenopathy was confirmed in all 113 patients: 75 (66.4%) were diagnosed with tuberculosis, 29 (25.7%) – mycobacterial infection, and 9 (8.8%) had a lymphoproliferative disease. The article presents the criteria for differential diagnostics between these diseases.